Comparison of space radiation GCR models to recent AMS data. (August 2018) - Norbury, John W.; Whitman, Kathryn; Lee, Kerry; Slaba, Tony C.; Badavi, Francis F.
Abstract: This paper is the third in a series of comparisons of American (NASA) and Russian (ROSCOSMOS) space radiation calculations. The present work focuses on calculation of fluxes of galactic cosmic rays (GCR), which are a constant source of radiation that constitutes one of the major hazards during deep space exploration missions for both astronauts/cosmonauts and hardware. In this work, commonly used GCR models are compared with recently published measurements of cosmic ray Hydrogen, Helium, and the Boron-to-Carbon ratio from the Alpha Magnetic Spectrometer (AMS). All of the models were developed and calibrated prior to the publication of the AMS data; therefore this an opportunity to validate the models against an independent data set.